Inhibition of ATR kinase with the selective inhibitor VE-821 results in radiosensitization of cells of promyelocytic leukaemia (HL-60) - Vávrová, Jiřina; Zárybnická, Lenka; Lukášová, Emilie; Řezáčová, Martina; Novotná, Eva; Sinkorová, Zuzana; Tichý, Aleš; Pejchal, Jaroslav; Durišová, Kamila (Radiation and environmental biophysics, 2013)
We compared the effects of inhibitors of kinases ATM (KU55933) and ATR (VE-821) (incubated for 30 min before irradiation) on the radiosensitization of human promyelocyte leukaemia cells (HL-60), lacking functional protein p53. VE-821 reduces phosphorylation of check-point kinase 1 at serine 345, and KU55933 reduces phosphorylation of check-point kinase 2 on threonine 68 as assayed 4 h after irradiation by the dose of 6 Gy. Within 24 h after gamma-irradiation with a dose of 3 Gy, the cells accumulated in the G2 phase (67 %) and the number of cells in S phase decreased. KU55933 (10 μM) did not affect the accumulation of cells in G2 phase and did not affect the decrease in the number of cells in S phase after irradiation. VE-821 (2 and 10 μM) reduced the number of irradiated cells in the G2 phase to the level of non-irradiated cells and increased the number of irradiated cells in S phase, compared to irradiated cells not treated with inhibitors. In the 144 h interval after irradiation with 3 Gy, there was a considerable induction of apoptosis in the VE-821 group (10 μM). The repair of the radiation damage, as observed 72 h after irradiation, was more rapid in the group exposed solely to irradiation and in the group treated with KU55933 (80 and 77 % of cells, respectively, were free of DSBs), whereas in the group incubated with 10 μM VE-821, there were only 61 % of cells free of DSBs. The inhibition of kinase ATR with its specific inhibitor VE-821 resulted in a more pronounced radiosensitizing effect in HL-60 cells as compared to the inhibition of kinase ATM with the inhibitor KU55933. In contrast to KU55933, the VE-821 treatment prevented HL-60 cells from undergoing G2 cell cycle arrest. Taken together, we conclude that the ATR kinase inhibition offers a new possibility of radiosensitization of tumour cells lacking functional protein p53.
Keywords: Leukemia, Promyelocytic, Acute; Morpholines; G2 Phase Cell Cycle Checkpoints; HL-60 buňky; pyraziny; kontrolní body fáze G2 buněčného cyklu; Pyrones; inhibitory proteinkinas; DNA Repair; pyrony; oprava DNA; Ataxia Telangiectasia Mutated Proteins; lidé; akutní promyelocytární leukemie; HL-60 Cells; tolerance záření; Humans; morfoliny; Protein Kinase Inhibitors; apoptóza; Radiation Tolerance; sulfony; Sulfones; Pyrazines; ATM protein; Apoptosis